DECONSTRUCTING CULTURAL IDENTITY IN RISHI REDDI’S KARMA AND OTHER STORIES - Adji, Alberta Natasia; Karnanta, Kukuh Yudha; Putra, Gesang Manggala Nugraha (Balai Bahasa Jawa Timur, 2018)
This article strives to deconstruct the main characters? cultural identity in Rishi Reddi?s short stories collection, entitled Karma and Other Stories, as the characters deal with their lives as Indian diaspora in the United States. The applied method is the close-reading technique. This article employs Jacques Derrida?s deconstruction by tracing the binary opposition found within the seven short stories; later they are to be disseminated so that the true meanign can be revealed. The article finds that (1) the emerging conflicts in the stories are caused by the strong ties of the protagonists toward Hinduism and Indian family tradition, with (2) their cultural identity has managed to align with modernity in the US, but (3) their ties to the core Hinduism and Indian principles will remain strong.